SURVIVAL OF TRANSGENIC MICE WITH PANCREATIC NEUROENDOCRINE TUMORS IS DETERMINED MORE BY HYPOGLYCEMIA SEVERITY THAN METASTATIC BURDEN - Inoue, Mitsuko; Inoue, Tomoyoshi; Tait, Madeline; Byrne, Thomas; McDonald, Donald (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES The purpose of this study was to compare the blood glucose and survival profiles of two strains of transgenic mice that develop pancreatic neuroendocrine tumors (PanNETs) with contrasting functionality and metastatic potential. METHODOLOGY Two strains of RIP1-Tag2 (RT2) transgenic mice that develop spontaneous PanNETs were compared: (1) RT2 mice in the C57BL/6J background (RT2;B6), and (2) hybrid RT2 mice (RT2;ABF1) generated by crossing RT2;B6 males to wild- type A/J females. Blood glucose, survival, and incidence of liver metastasis were compared in the two strains from age 8 to 17 weeks. RESULTS Blood glucose profiles and survival were similar in C57BL/6J mice and B6;A/J mice that lacked the RT2 transgene and did not develop PanNETs. By comparison, mean blood glucose values in RT2;B6 mice that had largely benign but functional PanNETs were 50% lower (44 mg/ dL) over the survey period than in RT2;AB6F1 mice (87.4 mg/dL) that had aggressive but non-functional PanNETs. Importantly, survival of RT2;B6 mice, which had only a 4% incidence of liver metastasis, was significantly less (35%) over 17 weeks than in RT2;AB6F1 mice (84%) that had a 47% incidence of liver metastasis. CONCLUSION Survival of transgenic mice with PanNETs is determined more by hypoglycemia severity than metastatic burden. PanNET insulin secretion is greater and survival shorter in RT2;B6 mice with rare metastases than in RT2;AB6F1 mice with frequent metastases. Tumor insulin secretion and hypoglycemia limit survival in RT2;B6 mice at an earlier age- more than the impact of liver metastases on increased mortality in RT2;AB6F1 mice.